Energy Harvesting from Waste Heat using Thermoelectric Generators - Bhalla Lalit; Siri Dharmapuri; Kakarla Udaya Sri; Singh Dhiraj; Bisht Deepa; Singh Amanveer; Yadav Kanchan; Alsalami Zaid (E3S Web of Conferences)
This research examines the synergistic benefits and impact of Thermoelectric Generators (TEGs) in energy harvesting, emphasizing their contribution to improving system efficiency via appropriate integration with energy management systems. The empirical findings indicate a significant 15% enhancement in energy conversion efficiency via enhanced waste heat recovery using TEGs, coupled with an 8% augmentation in total system performance attributable to sophisticated energy management strategies. Furthermore, there is a notable 10% decrease in energy losses, achieved by meticulous management of temperature gradients and regulation of power output. Total Energy Efficiency Metrics indicate a 12.5% enhancement in energy usage, a 2% decrease in system downtime attributable to the improved dependability of TEG units, and a 4°C reduction in average operating temperature, hence assuring increased lifespan of the devices. These findings underscore the practical advantages of integrating TEGs into waste heat recovery systems, enhancing the ongoing discussion on sustainable energy solutions by offering definitive proof of their effectiveness and the collaborative effect they exert on energy harvesting and system efficiency.